FL HOUSE OF REPRESENTATIVES 1992 CS/HB 1753 - FL HOUSE OF REPRESENTATIVES; COMMITTEE ON EMPLOYEE & MANAGEMENT RELATION (Tufts Archival Research Center, 2007)
Bill H.B.1753 in the state of Florida prohibiting employment discrimination based on use of legal agricultural substances during non-working hours.